Good governance as a strategic choice in brownfield regeneration: Regional dynamics from the Czech Republic. (April 2018) - Klusáček, Petr; Alexandrescu, Filip; Osman, Robert; Malý, Jiří; Kunc, Josef; Dvořák, Petr; Frantál, Bohumil; Havlíček, Marek; Krejčí, Tomáš; Martinát, Stanislav; Skokanová, Hana; Trojan, Jakub
Highlights: Involvement of public administration in brownfields regeneration projects is crucial. Active participation of different groups of actors is very important. Transparency is key precondition for the succesfull joint cooperation of actors. Shrinking regions and municipalities have ussually the highest motivation. Good governance is an added value to the simple economic attractiveness of brownfield regeneration. Abstract: The application of principles of good governance in brownfield regeneration, for instance through improved transparency and participation of various groups of stakeholders, varies between regions and cities. In this article, we approach good governance as a strategic response of actors in the struggle for creating development opportunities on brownfield land. Good governance has been mostly seen as a normative consideration, but it is not clear why regions with lower development prospects would employ it more than better developed regions, as it recently happened in the Czech Republic. We assume that the public administration at the regional and municipal level plays an active role in divising strategies to attract investors for brownfield redevelopment. This process brings public administrations in interaction with each other and with investors, regulators and civil society groups within a society-wide brownfield redevelopment field. This field is an arena where all these different actors struggle for redeveloping their brownfield land. Regional and municipal administrations from developed regions stand to benefit from their higher economic growth potential and hence have a dominant position within the field. We identify the latter as the incumbents or "power-holders" of the national brownfield regeneration field. Less developed regions have lower attractiveness for brownfield redevelopment, which places them in a subordinate position in the field. They are so-called challengers that are likely to favor alternative strategies for their brownfields, going beyond mere economic attractiveness. By comparing differently developed regions and regional capitals in the Czech Republic, we show how some challengers use good governance, such as responsiveness, participation and transparency, as an alternative strategy to attract investors despite their economic predicament. For regional capitals, however, good governance is practiced both by highly developed and less developed cities. We draw evidence from interviews with key stakeholders and socio-economic data at the regional and municipal level in the Czech Republic. In the conclusion, we show some of the identified limitations in good governace, such as obstacles to participation, responsiveness or transparency, and how they can be recognized and overcome.